Mammographic breast density and characteristics of invasive breast cancer. (February 2021) - Pizzato, M.; Carioli, G.; Rosso, S.; Zanetti, R.; La Vecchia, C.
Highlights: High breast density was inversely associated with grade. No associations with hormonal tumour characteristics were observed. Breast adipose cells may support an environment favourable to higher grade tumours. Abstract: Introduction: Inconclusive data exist on the association between breast density and breast cancer characteristics. Materials and methods: We conducted a case-only study on 667 invasive breast cancers, using data from the Piedmont Cancer Registry. We applied a multivariate logistic regression model to estimate odds ratios (ORs) and the corresponding 95% confidence intervals (CIs) of high breast density (Breast Imaging Reporting and Data System, BI-RADS 3−4) versus low (BI-RADS 1−2) in relation to histologic grade, pathological tumour size and lymph node status, histotype, estrogen and progesterone receptor, HER2 and Ki67 status. Histopathological data were assessed according to the American Joint Committee on Cancer (AJCC) Staging Manual guidelines. The model includes terms for age at diagnosis, education level, body mass index, reproductive factors, family history of breast cancer, smoking and diabetes. Results: As regards histologic grade, compared to well differentiated tumours, the OR of high (versus low) breast density cases was 0.61 (95% CI 0.38−0.98) for moderately-poorly differentiated tumours. No other associations with hormonal and histopathological characteristics were observed. Discussion: Our results indicate that low breast density is associated with moderately-poorly differentiated breast tumours.